T-pattern detection in the scientific literature of this century: A systematic review - Anguera, M. Teresa; Jonsson, Gudberg K.; Escolano-Pérez, Elena; Sánchez-Lopez, Carmen Rosa; Losada, José Luis; Portell, Mariona (Frontiers in Psychology, 2023)
The aims of this study were: 1) to carry out a systematic review of the literature on T-Pattern analysis, and 2) to explore the possible contribution of mixed methods research to the integration of qualitative and quantitative elements on a synthesis level. Based on PRISMA guidelines, searches were carried out in the Scopus, PsycINFO and Web of Science databases. The general search syntax was: “THEME” AND (“T-Patterns” OR “T-Patterns”) carried out in title, keywords and abstract. In addition, we included empirical articles on THEME and T-Patterns collected in other sources based on citations in several empirical works and consultations with different authors. This selection process resulted in 100 primary documents making up this systematic review. The results showed that the detection of structures in behavior patterns forms a nexus between studies carried out in very diverse fields and contexts. Most studies are observational, whilst the applicability and power of T-Pattern detection are extraordinary. It allows the researcher to go deeper in a robust analysis that responds to the integration of qualitative and quantitative elements which constitutes the leitmotif of mixed methods; and also to discover the deep, hidden structure that underlies the respective databases, regardless of the methodology used in each study. The possibilities in assigning parameters notably increase the options for obtaining results and their interpretation.